Analisa Sifat Mekanis Beton Mutu Tinggi dengan Pemakaian Fly Ash lebih dari 50% Sebagai Pengganti Semen dan Superplasticizer - Widiyanto, Eko; , Mochamad Solikin, S.T., M.T., Ph.D (2016)
Concrete is main construction material. So now a lot of research is conducted to improve the quality of concrete in order to achieve a better quality of the concrete. The use of fly ash as a partially cement substitute on materials is one of the innovations that are efficient in reducing the use of cement. Moreover the use fly ash reduce waste material and environmental pollution resulting from coal power plant combustion and reduce the cost of production of the manufacture of concrete. In this research the strenght design of high volume fly ash concrete is 45 MPa. In with variation of fly ash 0%, 50%, 60% and 70%, in addition the water binder ratio is 0,35 and 0,4 % sika viscocrete 1003 was used to achieved the workability design. For compressive strenght, test after curing for 28 dan 56 days. The dimension of specimen is 15 cm in diameter and 30 cm in high. As well as for splitting tensile strenght by the age 56 days was tested after curing with specimen like specimen to testing compresive strength, also the specimen diameter 10 cm and height 5 cm was used for water absorption test. The result show that the slump value is ± 10 cm. Then at 28 days tested and obtained the highest compressive strength value of 25 MPa, then at the age of 56 days highest compressive strength values obtained of 47 MPa. The Value of maximum splitting tensile strength is 12 MPa and lowest water absorption value is amounting to 2.462%. The compressive strength and splitting tensile strength of concrete that is using variations 50% of fly ash produce the same concrete with using 100% of cement. The compressive strength and splitting tensile strength decreased with increasing variation of fly ash is more than 50% which is at 60% and 70%. Absorption capacity in concrete using fly ash was lower than the concrete using 100% of cement and the value decline rapidly with variations of fly ash used.